2019
DOI: 10.1017/aee.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Hegemony, Counter-Hegemony and Food Systems Literacy: Transforming the Global Industrial Food System

Abstract: National and global food systems are beset by intersecting and mutually reinforcing crises of public and ecological health. The locus of these crises resides primarily in the excessive concentration of corporate power and control. Deploying a Gramscian theory of politics as a contribution to the ongoing development of a critical food-based environmental education pedagogy, this article argues that transformative change requires the mass exercise of food citizenship directed towards the realisation of a sociall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
0
17
0
5
Order By: Relevance
“…Neoliberal advocates count on "the market as the final arbiter of efficient economic policy...walling off powerful economic actors and industrial forces from popular accountability and local responsibility" (Andrée et al, 2014, p. 11). Meanwhile, food sovereignty advocates call for a reorganizing of food production, distribution, and consumption patterns that contests the common understanding that large-scale agriculture is better and more efficient than small-scale farming (Massicotte, 2014;Meek & Tarlau, 2016;Rose & Lourival, 2019). In Canada, food sovereignty activists, including members of the National Farmers Union, emphasize the productive and reproductive roles of food producers who contribute and seek innovative methods to maintain and/or promote agroecological practices.…”
Section: Critical Pedagogy and Food Literacy Towards Food Sovereigntymentioning
confidence: 99%
See 2 more Smart Citations
“…Neoliberal advocates count on "the market as the final arbiter of efficient economic policy...walling off powerful economic actors and industrial forces from popular accountability and local responsibility" (Andrée et al, 2014, p. 11). Meanwhile, food sovereignty advocates call for a reorganizing of food production, distribution, and consumption patterns that contests the common understanding that large-scale agriculture is better and more efficient than small-scale farming (Massicotte, 2014;Meek & Tarlau, 2016;Rose & Lourival, 2019). In Canada, food sovereignty activists, including members of the National Farmers Union, emphasize the productive and reproductive roles of food producers who contribute and seek innovative methods to maintain and/or promote agroecological practices.…”
Section: Critical Pedagogy and Food Literacy Towards Food Sovereigntymentioning
confidence: 99%
“…Numerous studies have demonstrated that agriculture and agrifood systems 1 are key contributors to environmental protection or degradation and anthropogenic climate change (Gliessman, 2018;Anderson et al, 2021). This is especially evident since the late 1980s, with the globalizing corporate food regime that spread from Europe and the United States to most parts of the world (Andrée et al, 2014;Friedman & McMichael, 1989;Rose & Lourival, 2019). This corporate regime has the set of norms and rules that govern today's dominant agrifood system, which is based on the expansion of large-scale, capital, and energy intensive agricultural production (i.e., fertilizers, pesticides, water).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food literacy is an emerging term which attempts to more comprehensively describe the knowledge, skills and behaviours used to meet food needs, inclusive of these elements, in an effort to better reflect contemporary food and eating [21]. The widespread use of this term has spanned continents, and reflects a diverse range of food related outcomes from chronic disease risk, to lifeskills, ecological sustainability and economic grow [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Cf. Bowers, 2008; Martusewicz, 2014; Iared, Tullio, Payne and de Oliveira (2015); Valenti, de Oliveira and Logarezzi (2017); Edwards, Hill and Boxley (2018), Wildemeersch (2018), Rose and Lourival (2019), Mann (2019); cf. Huckle's Critical School Geography , https://john.huckle.org.uk/contents/.…”
mentioning
confidence: 99%